An Exploratory Survey of Deqi Sensation from the Views and Experiences of Chinese Patients and Acupuncturists. (21st November 2013) - Yuan, Hong-Wen; Ma, Liang-Xiao; Zhang, Peng; Lin, Chi; Qi, Dan-Dan; Li, Jing; Xin, Si-Yuan; Hu, Ni-Juan; Li, Chun-Hua; Liu, Yu-Qi; Hao, Jie; Xie, Jie-Ping; et al.
Abstract : Deqi sensation is believed to be important in clinical efficacy according to TCM theory. The measuring method of Deqi sensation has significant implications for the result of research trials. This study makes an investigation on acupuncture-experienced patients and expert acupuncturists in China and aims to find out the patient's needling sensations and acupuncturist's sensations which can be acceptable as descriptors of Deqi sensation, so as to provide foundation for more systematic and sensitive quantitative evaluation method of Deqi sensation. Results of this survey indicated that the Deqi sensation noted by both patient and acupuncturist is equally important to the treatment efficacy. It is found that there are some differences between the patients' real-life experience and the acupuncturists' expectations on patients' Deqi sensation. The "dull pain, " "aching, " "sore, " "numb, " "distended, " "heavy, " "electric, " "throbbing, " "warmness, " "coolness, " "spreading, " and "radiating" can be considered as the main manifestations of Deqi sensations. The acupuncturists believed that Deqi sensations were mainly "pulling, " "tight, " and "throbbing." We suggest developing a questionnaire measuring the Deqi sensations which includes both the sensations of the patient and acupuncturist, and this would be very important and necessary for a better understanding of the relationship between Deqi sensation and acupuncture effects in future studies.